Long PFN in unstable subtrochantric fracture with absent lateral wall support in proximal fragment with delayed augmentation with encircalage wire and bone grafting - Kamble, Sudarshan A.; Bharti, Sanjay R.; Rathod, Jay Rundan (International Journal of Research in Medical Sciences, 2017)
In 1949 Boyd and Griffin Subtrochanteric fracture femur as a variant of peritrochanteric fracture with higher incidence of unsatisfactory result both in the elderly and young. Most of this fracture is with higher incidence of unsatisfactory result after operative treatment This single case study shows one of the unpredicted iotrogenic complications. Material and method: Patient is 78yr female patient with multiple co-morbid conditions with subtrochanetric fracture. Surgery was done with long PFN nail inserted with good purchase in head, reduction check under C-arm with in antero-posterior & lateral view shows little malreduction and nail is out of medulary cavity in proximal fragment. Revision in same sitting not possible due to some medical reasons. Revision surgery done after fitness and reduction held with encieclage wire and bone grafting done. Conclusion: Even without lateral wall support if there is good purchase of screws in head and shaft, there will be good union and good functional outcome.